Progress in our understanding of the pathogenesis of ankylosing spondylitis. (16th November 2018) - Simone, Davide; Al Mossawi, M Hussein; Bowness, Paul
Abstract: AS is a common rheumatic condition characterized by inflammation and new bone formation. The pathogenesis of AS is likely multifactorial and has not been fully elucidated to date. A major genetic role has been demonstrated. The strongest genetic association is with HLA B27. Numerous other associated genetic polymorphisms have been identified, including those affecting the type 17 immune pathway, although the precise link between genetics and pathogenesis remains unexplained. Several immunological alterations, together with recent therapeutic advances, support a central role for IL-23- and IL-17-producing immune cells in disease pathogenesis. Recently, perturbations of gut microbiota of AS patients have further catalysed research and offer potential for future therapeutic intervention. In this review we outline the genetic basis of AS and describe the current hypotheses for disease pathogenesis. We synthesize recent experimental research data and clinical studies to support a central role for the type 17/23 immune axis in AS.